Pengaruh Kualitas Produk, Kualitas Layanan Dan Wom Terhadap Keputusan Pembelian Konsumen Restoran Mie Ayam Ny Wong, Jakarta - Tirto Hadi; Fathorrahman; Theresia Pradiani (Lembaga Riset Ilmiah, Yayasan Mentari Meraki Asa, 2023)
A lot of facts and data are mentioned about how significantly culinary business affect Indonesia. It is not simply the business related with human basic needs, more that culinerarypreneurficantly in term of economic. Among those culinerarypreneur, there is a humble restaurant, named Mie Ayam Ny Wong, in Gandaria, Kebayoran Baru, South Jakarta. Something that makes the restaurant unique is that, in term of size, it is very small; they use the veranda and garage as a dining area; they run the business conventionally without marketing activity. But the strange is, the restaurant is always full. This objective of the research is to analyze the effect of product quality, service quality, word of mouth on the purchase decision. The subject of the study are all the consumers of the restaurant with purposive sampling size of 100 respondent who ordered chicken noodle and have dinning on site. The research is analysed by multiple linear regression The result of the study shows that the product qulaity has no effect on purchase decision. The other around, service quality and word of mouth has positive and significant effect to the purchase decision. In addition, product quality, service quality and word of mouth simultaniously give effect on purchase decision.